Investigación de mercados para determinar la posibilidad de habilitar el bachillerato en Administración de Empresas en la modalidad diurna en el Campus Tecnológico Local de San José o el Centro Académico de Alajuela - Quesada-Solís, María José (Instituto Tecnológico de Costa Rica, 2019)
This investigation research is the result of the desire of the School of Business Administration of the Tecnológico de Costa Rica, to know if this career, in a diurnal way, is a viable option in terms of internal demand for the current students from the Campus Tecnológico Local de San José, or, Centro Académico de Alajuela. The objetive with this, a research was designed a mixed approach where a sample composed of 236 current students of the career of Business Administration of the Tecnológico de Costa Rica enrolled in the plan 231 of the Campus Tecnológico Central Cartago and the plan 232 was studied from the Campus Tecnológico Local de San José, through a stratified sampling, to maintain the representativeness of both student’s populations, and for convenience in terms of the ease of contact with each of the populations. The research daring as the main result, for which of the two educational centers of the Tecnológico de Costa Rica, Campus Tecnológico Local de San José or Centro Académico de Alajuela, there is a greater demand on the part of the students surveyed in reference to the career of Business Administration, in its diurnal way, therefore, in which of them is more convenient to the School of Business Administration and enable the career in this mode. The research showed that 91% of the students surveyed prefer the Campus Tecnológico Local de San José so that the daytime career is enabled, mainly because the students surveyed consider that the current 232 schedule puts their safety at risk. In addition to presenting the main results of the research, a series of recommendations were made to the School of Business Administration, based on them.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, 2019.
Keywords: Instituto Tecnológico de Costa Rica. Campus Tecnológico Local San José; Investigación de mercados; Marketing; Mercadeo